The Experience of Transcendental Communication in Tahajud Prayer Among TikTok User @dynsonlyy - Syaifuddin Syaifuddin; Atef Fahrudin; Galang Ikhwan Aji Sabda (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
The digital era transforms religious practices such as Tahajud prayer into a spiritual experience publicly shared and reinterpreted through social media, creating a new reality of transcendental communication within digital spaces. This study aims to understand the meaning of transcendental communication in Tahajud prayer shared by the TikTok user @dynsonlyy through virtual ethnographic analysis of comments and digital interactions. This research employs mixed methods with a sequential explanatory design, combining virtual ethnography, descriptive quantitative analysis, netnography, methodological triangulation, and data visualization to understand transcendental communication comprehensively. Research findings: The study reveals that transcendental communication through Tahajud prayer on TikTok is personal, collective, and significantly impactful. From 309 analyzed comments, 88 experiences related to sustenance (rezeki), 63 to inner peace, 52 to education issues, 46 to finance, 41 to family, and 40 to work were identified. One hundred fifty-six comments contained prayer requests, 96 reflected emotional transformation, and 29 noted mystical experiences. TikTok functions as a sacred digital space, enabling authentic spiritual expression and forming a networked religious community, strengthening religious identity while serving as a medium for collective coping and spiritual transformation in the digital era. Conclusion: Transcendental communication in Tahajud prayer on TikTok evolves into digital communal spirituality, dominated by prayer requests and sustenance outcomes, demonstrating real psychological and material effects.